2004
DOI: 10.4049/jimmunol.172.8.4893
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Blockage Increases Resistance to Infection with the Intracellular ProtozoanTrypanosoma cruzi

Abstract: Recent studies have revealed an important role for CTLA-4 as a negative regulator of T cell activation. In the present study, we evaluated the importance of CTLA-4 to the immune response against the intracellular protozoan, Trypanosoma cruzi, the causative agent of Chagas’ disease. We observed that the expression of CTLA-4 in spleen cells from naive mice cultured in the presence of live trypomastigote forms of T. cruzi increases over time of exposure. Furthermore, spleen cells harvested from recently infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 62 publications
3
43
0
3
Order By: Relevance
“…In fact, the blockade of PD-1 and PD-L1 or deletion of the PD-1 gene ameliorated the control of parasite burden both systemically and in cardiac tissue. Similar to our current results, we previously reported that T. cruzi induces upregulated expression of another coinhibitor molecule, CTLA-4, in lymphocytes in vivo and in vitro, and the blockade of this inhibitory signaling pathway lead to increased inflammation and decreased tissue parasitism (23).…”
Section: Discussionsupporting
confidence: 80%
“…In fact, the blockade of PD-1 and PD-L1 or deletion of the PD-1 gene ameliorated the control of parasite burden both systemically and in cardiac tissue. Similar to our current results, we previously reported that T. cruzi induces upregulated expression of another coinhibitor molecule, CTLA-4, in lymphocytes in vivo and in vitro, and the blockade of this inhibitory signaling pathway lead to increased inflammation and decreased tissue parasitism (23).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that CD28-deficient mice were highly susceptible to T. cruzi infection, presenting with higher parasitemia and tissue parasitism but less inflammation in the heart than those of wildtype mice (28). Moreover, it has been shown that modulation via CTLA-4 during the acute phase of experimental infection leads to a decreased ability to clear the parasite and, thus, susceptibility to T. cruzi infection (29). Our previous findings have shown that chagasic patients, despite their clinical form, showed decreased expression of CD28 by freshly isolated T cells compared to that of noninfected individuals (9,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the role of costimulatory molecules in murine infection with T. cruzi. It has been shown that mice that are deficient in CD28 are highly susceptible to T. cruzi infection (28), whereas CTLA-4 blocking increases resistance to infection (29). In humans, it has been demonstrated that chagasic patients have a higher frequency of CD28 Ϫ T cells in their bloodstream and that these cells display a heterogeneous repertoire (9,30).…”
mentioning
confidence: 99%
“…Although inhibitory receptor expression on T cells is an indicator of Ag elimination failure, these receptors are important for self-tolerance and the prevention of autoimmunity (12). The increased expression of CTLA-4 and PD-1 in lymphocytes has been described in acute T. cruzi mouse infection, and as expected (15,(88)(89)(90), the blockade of these inhibitory receptors decreases parasitemia and parasitism and increases inflammation and mortality (91,92). In this article, we report increased inhibitory receptor expression on CD8 + T cells in patients with severe forms of the disease, which, consistent with other chronic infections (12), could be implicated in the alteration of CD8 + T cell polyfunctionality.…”
Section: Cd8mentioning
confidence: 99%